Effect of meteorological parameters on plant growth and fruit quality of Kinnow mandarin - DOLKAR, DISKET; BAKSHI, PARSHANT; KACHROO, DILEEP; KOUR, KIRAN; KUMAR, RAKESH; SHARMA, NIRMAL; SINGH, AJITPAL (The Indian Journal of Agricultural Sciences, 2018)
Experiment was carried out to study the impact of climatic factors on growth and quality of Kinnow mandarin for two years (2014 and 2015). The results revealed that during first year, plant height was positively influenced by maximum and minimum relative humidity at K4 (period from maximum fruit set to fruit harvest) stage, whereas the stock girth and scion girth was positively favoured by both temperature gradients and relative humidity at K4 stage. Whereas, in second year, plant growth and fruit quality parameter were influenced positively by both maximum and minimum temperature and relative humidity at K4 stage. The titratable acidity content of juice had a positive relation with the maximum and minimum temperature and evapotranspiration at K4 stage.